Reappraising the psychosomatic approach in the study of “chronic orofacial pain”: looking for the essential nature of these intractable conditions - Toyofuku, Akira; Matsuoka, Hirofumi; Abiko, Yoshihiro (Frontiers in Pain Research, 2024)
As burning mouth syndrome (BMS) and atypical odontalgia (AO) continue to remain complex in terms of pathophysiology and lack explicit treatment protocol, clinicians are left searching for appropriate solutions. Oversimplification solves nothing about what bothers us in clinical situations with BMS or AO. It is important to treat a complicated phenomenon as complex. We should keep careful observations and fact-finding based on a pragmatic approach toward drug selection and prescription with regular follow-up. We also need to assess the long-term prognosis of treatment with a meticulous selection of sample size and characteristics. Further investigation of BMS and AO from a psychosomatic perspective has the potential to provide new insight into the interface between brain function and “chronic orofacial pain.”